Synthesis of Chitosan-PEGDA Hydrogels for Periodontal Applications - Krit Rattanawonsakul; Manissara Joynusaeng; Nattapat Klakhaeng; Jeerawan Thanarak (My University, 2025)
This study aims to fabricate and optimize hydrogels scaffold, based on chitosan and polyethylene glycol diacrylate (PEGDA). While the ultimate goal is to develop a site-specific drug delivery system for periodontal therapy, the present work focuses on the synthesis and characterisation of the hydrogel materials. The synthesis protocols for both scaffolds are optimised and evaluated in this work. Water contact angle measurements are conducted to assess surface wettability, an important factor influencing tissue interaction. Results show that PEGDA hydrogels possess higher hydrophilicity than chitosan, which may contribute to improved drug release performance in future applications. This research lays the groundwork for developing biocompatible, adhesive hydrogel systems for targeted periodontal treatment.
Keywords: Electrospun Nanofibers in Biomedical Applications; Hydrogels: synthesis, properties, applications; Advanced Drug Delivery Systems